Rester au Prêcheur - Justine Caussanel; Camille Chastanet; Marion Savignon; Félicien Pecquet-Caumeil (Projets de Paysage)
In the face of different natural hazards combined with rising water levels, how should we rethink our modes of existence? The municipality of Le Prêcheur, located in Northern Caribbean region of Martinique, is subject to a wide variety of recurring natural events and living in such an environment entails potential risks. Environmental questions linked to these risks and land tenure issues relating to informal housing will have to be taken into consideration in future urban planning and land use projects. At the crossroads of ecology and economics, the dynamics of the natural environment provide data which need to be used in urban planning. In a fragile context, an urban planning project cannot be represented in a single set form. Climatic events and societies evolve over time making it necessary to accept the initiation of a process that may only be continued by future generations if it is implemented as from today. The project is intended to achieve its goals by 2100 and to be implemented by means of tools fostering joint actions by residents and elected representatives to build a vision of the future for Le Prêcheur.